Biodiesel from corn germ oil catalytic and non-catalytic supercritical methanol transesterification. Issue 13 (2nd July 2016) - Demirbas, Ayhan
ABSTRACT: Transesterifications of grain of corn oil samples in KOH catalytic and in supercritical methanol were studied without using any catalyst. Biodiesel, an alternative biodegradable diesel fuel, is derived from triglycerides by transesterification with methanol and ethanol. The transesterification reaction is affected by the molar ratio of glycerides to alcohol, catalysts, reaction temperature, reaction time and free fatty acids and water content of oils or fats. It was observed that increasing the reaction temperature, especially to supercritical temperatures, had a favorable influence on methyl ester (biodiesel) conversion. The molar ratio of methanol to corn germ oil is also one of the most important variables affecting the yield of methyl esters. Higher molar ratios result in greater ester production in a shorter time. In the transesterification, free fatty acids and water always produce negative effects, since the presence of free fatty acids and water causes soap formation, consumes catalysts, and reduces catalyst effectiveness, all of which result in a low conversion.